Work Lung Disease Due to Grain Dust - Ariani Permatasari; Reagen Irwan Kolibu (Faculty of Medicine Universitas Airlangga, 2020)
Indonesia is one of the third largest rice producers globally; therefore, grain dust-related lung diseases will be more significant. rain dust is easily exposed to humans, triggers lung damage, and decline the lung function. Grain dust exposure is associated with occupational lung diseases, for instance, acute reversible airflow obstruction, chronic obstructive pulmonary disease, grain fever, organic dust syndrome, and hypersensitivity pneumonitis. Smoking and the environment might aggravate grain dust-related respiratory problems. The average tolerated dose of grain dust is about less than 3 mg/m3. Avoiding exposure to grain dust is primer prevention.